On the Systemic Assessment of a Sustainable University - Gonella, Francesco (Journal of Environmental Accounting and Management, 2026)
In this paper, some motivations are discussed for an integrated approach in the study of complex environmental and socio-economic systems, based on the necessity of a systemic perspective wherever the drivers and the flows that control a system stability and evolution are strictly con- nected each other. The validity and the efficacy of the emergy-based analysis is then outlined for the general sustainability assessment of a University, and in particular for Venice Ca’ Foscari University in Italy.